2009
DOI: 10.1098/rspb.2008.1919
|View full text |Cite
|
Sign up to set email alerts
|

Angiosperm leaf vein evolution was physiologically and environmentally transformative

Abstract: The veins that irrigate leaves during photosynthesis are demonstrated to be strikingly more abundant in flowering plants than in any other vascular plant lineage. Angiosperm vein densities average 8 mm of vein per mm 2 of leaf area and can reach 25 mm mm K2 , whereas such high densities are absent from all other plants, living or extinct. Leaves of non-angiosperms have consistently averaged close to 2 mm mm K2 throughout 380 million years of evolution despite a complex history that has involved four or more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
461
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(494 citation statements)
references
References 38 publications
23
461
2
Order By: Relevance
“…For example, a large leaf may be selected for a plant of a moist area, for effective light capture and photosynthesis relative to biomass allocation 44 , and a small leaf may be selected in drought-tolerant species 8 ; both may have high minor vein densities, enabling high photosynthetic rates when water is available. The potential of angiosperms to vary strongly in vein density enables dominance in a far greater range of habitats than other plant lineages 3,6,48 , especially as leaf size can adapt independently to optimise other ecological benefits against costs 6,7,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a large leaf may be selected for a plant of a moist area, for effective light capture and photosynthesis relative to biomass allocation 44 , and a small leaf may be selected in drought-tolerant species 8 ; both may have high minor vein densities, enabling high photosynthetic rates when water is available. The potential of angiosperms to vary strongly in vein density enables dominance in a far greater range of habitats than other plant lineages 3,6,48 , especially as leaf size can adapt independently to optimise other ecological benefits against costs 6,7,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Across species, leaf venation shows enormous structural diversity, the more remarkable because of its shared development and functions. The functional consequences of leaf venation have attracted increasing interest in a widening range of fields, because vein traits, including vein diameters and densities ( = length per leaf area), as well as leaf size are key determinants of plant performance and indeed of shifts in the lineages that dominated the world vegetation through deep time [1][2][3][4][5][6][7][8][9] .…”
mentioning
confidence: 99%
“…Cramer et al 2001). However, this capacity to move water from soil to atmosphere has not been uniform through time: the flowering plants that now dominate most terrestrial environments recently have been shown to have unparalleled capacities to transpire water (Boyce et al 2009). Because water loss is an inevitable component of leaf gas exchange, photosynthesis is limited by the ability of the plant to replace water lost through transpiration.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to infer environmental conditions from seed fern structures using extant plants as models should be viewed with considerable caution, particularly where the extant plants are angiosperms. Consider, for example, the large differences in leaf architecture, as related to leaf physiology, documented between angiosperms and all other plant groups (Boyce, 2008;Boyce et al, 2009.…”
Section: Discussion: Ecological Re-evaluationmentioning
confidence: 99%
“…In contrast with these findings about transpirative capacity, however, the medullosans also have been shown to have had capacities for rapid transport of water through their vascular systems to the point of dispersal to the atmosphere, as did vine-like lyginopterid seed ferns and the ground-cover sphenopsid scrambler, Sphenophyllum (Wilson et al, 2008;Wilson and Knoll, 2010). This presents us with somewhat of a dilemma -based on the work of Wilson et al (2008) and Wilson and Knoll (2010), some Pennsylvanian plants, including medullosans, had the capacity to get water to the evaporative surfaces nearly as rapidly and efficiently as some flowering plants, while, based on the work of Boyce et al (2009, these same plants seem to lack the ability to vent that water to the atmosphere at a rate comparable to its uptake and transport. The key to this may be the scaling of total evaporative surface area of the leaf array relative to the total water transport capacity of the stem and leaf -which ought to be in balance.…”
Section: Additional Considerationsmentioning
confidence: 99%